(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The active participation of the Crimean Tatars deported to Central Asia in the socio-political and cultural life of Turkestan is clearly visible from the second half of the 19th century. After all, historical processes take place before they are written. Any past events have their own laws, objective and subjective sides. For example, history encourages thinking, observation, and learning. In this sense, the fate of the Crimean Tatars deported to Central Asia and their role in the socio-political and cultural life of Turkestan is important. Because this is a special stage in the cooperation of the Turkic peoples. This article describes the historiography of Crimean Tatars, who were deported to Central Asia, active participation in the sociopolitical and cultural life of Turkestan.